Handbook on the toxicology of metals. - Nordberg, Gunnar; Costa, Max (Academic Press, 2022)
Handbook on the Toxicology of Metals, Fifth Edition, Volume I: General Considerations is the first volume of a two-volume work that gives an overview and covers topics of general importance including reviews of various health effects of trace metals. The book emphasizes toxic effects in humans, along with discussions on the toxic effects of animals and biological systems in vitro when relevant. The book has been systematically updated with the latest studies and advances in technology and contains several new chapters. As a multidisciplinary resource that integrates both human and environmental toxicology, the book is a comprehensive and valuable reference for toxicologists, physicians, pharmacologists, and environmental scientists in the fields of environmental, occupational and public health.